An integrative model for the filtration efficiencies in realistic tests with consideration of the filtration velocity profile and challenging particle size distribution. Issue 2 (1st February 2017) - Sachinidou, Panagiota; Bahk, Yeon Kyoung; Wang, Jing
ABSTRACT: Many well-established models can be applied to calculate the filtration efficiencies. In these models the filtration velocity and challenging particle size are assumed to be known accurately. However, in realistic filtration tests, the filtration velocity has profiles dependent on the filter holder geometry and experimental conditions; the challenging particles have size distributions dependent on the instruments and operation conditions. These factors can potentially affect the measured filtration efficiency and lead to discrepancies with the models. This study aims to develop an integrative model to predict the filtration efficiencies in realistic tests by incorporating the effects of the filtration velocity profile and challenging particle size distribution classified by a differential mobility analyzer (DMA) into the existing filtration models. Face velocity profile is modeled with fluid mechanics simulations; the initial generated particle size distribution, the particle charging status and the DMA transfer function are modeled to obtain the challenging particle size distribution. These results are then fed into the filtration models. Simulated results are compared with experimental ones to verify the model accuracy. This model can be used to reduce filtration test artifacts and to improve the experimental procedure. The results reveal that the face velocity upstream the filter exhibits high degree of homogeneity not affecting the filtration efficiency if the filter pressure drop is not very low. The generated particle size distribution and the DMA selection size window could influence the challenging particle size distribution and therefore the measured filtration efficiency. Copyright © 2017 American Association for Aerosol Research